The Effect of Foreign Investment And Domestic Investment on The Gross Regional Domestic Product in Indonesia (Survey of 34 Provinces for 2019-2022) - Ali, Muhammad; Agustina, Ingrid Larasati; Apriliana, Tria; Ikram, Syafrizal; Suryana, Suryana; Hadi, Dudi Abdul (Universitas Batanghari Jambi, 2024)
The purpose of this study was to determine the effect of foreign investment and domestic investment on gross regional domestic product in Indonesia. The research subjects are 34 provinces in Indonesia for the period 2019 – 2022. This research was conducted in Indonesia. This type of research is quantitative research. The data used in this study are secondary data obtained from the Indonesian Central Bureau of Statistics. The research method used in this study is the explanatory method. Data analysis techniques in this study are descriptive analysis and panel data regression analysis. The results of this study simultaneously indicate that there is an influence of foreign investment and domestic investment on gross regional domestic product. Partially, there is no effect of foreign investment on gross regional domestic product, while domestic investment has an effect on gross regional domestic product.